The reality built through the architectural model: A teaching-learning experience in high school - Rodríguez Méndez, Fco. Javier; García Gago, Jesús Mª (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The construction of architectural models as a pedagogical tool applied in the high school stage allows the student to understand the analyzed building architecturally, while increasing their spatial vision, becoming familiar with the use of architectural plans. In addition, the historical study of the building, in this case, in which he has developed his studies in recent years, initiates him in the habit of university research, getting involved from the beginning in achieving the objectives set, so this type of projects can be considered an interesting teaching-learning experience.